Microbiological and Chemical Investigation of Drinking Water Samples on the Operational Area of Pannon Víz Zrt. - Kovács, Zsófia; Miseta, Roland; Zseni, Anikó (International Journal of Engineering and Management Sciences, 2018)
In our research the potable water quality was monitored between 1 January 2015 and 31 October 2017 in the operational area of Pannon-Víz Zrt. The connection between temperature, microbiological load and chemical parameters were investigated. After evaluating data, the following results have been identified. The seasonal changes of the microbiologically positive samples are determined by the contamination caused by Escherichia coli, Enterococci and Pseudomonas aeruginosa. The coliform group and the 22°C and 37°C colony-form units showed no seasonal dynamics. The analysed chemical parameters were below the limit during the examined period. Based on the correlation analysis, there is no correlation between chemical and microbiological parameters.